2001
DOI: 10.1046/j.1365-2249.2001.01613.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigen processing for MHC class I restricted presentation of exogenous influenza A virus nucleoprotein by B-lymphoblastoid cells

Abstract: SUMMARYIn general, exogenous proteins are processed by antigen-presenting cells in the endosomes for major histocompatibility complex (MHC) class II presentation to CD41 T cells, while proteins synthesized endogenously are processed in the cytoplasm for MHC class I presentation to CD8 1 T cells. However, it is recognized that exogenous proteins can be processed for MHC class I presentation also, and evidence in favour of alternatives to the conventional MHC class I processing and presentation pathway is accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Of the 7 directly discovered influenza A virus ligands, only the NP 418-426 peptide contains the I-A b binding motif. However, it is unlikely that the NP 418-426 IFN-␥ response generated by lymphocytes isolated from PR8 infected HLA-B*0702 transgenic mice is largely because of CD4 T cell reactivity given that the NP 418-426 epitope elicits CD8 T cell reactivity during in vitro stimulation of human peripheral blood mononuclear cells (PBMC) isolated from healthy HLA-B*0702 and -B*3501 adults (13,(22)(23)(24).…”
Section: Comparative Mass Spectrometry Reveals 7 Influenza Hla B*0702mentioning
confidence: 99%
“…Of the 7 directly discovered influenza A virus ligands, only the NP 418-426 peptide contains the I-A b binding motif. However, it is unlikely that the NP 418-426 IFN-␥ response generated by lymphocytes isolated from PR8 infected HLA-B*0702 transgenic mice is largely because of CD4 T cell reactivity given that the NP 418-426 epitope elicits CD8 T cell reactivity during in vitro stimulation of human peripheral blood mononuclear cells (PBMC) isolated from healthy HLA-B*0702 and -B*3501 adults (13,(22)(23)(24).…”
Section: Comparative Mass Spectrometry Reveals 7 Influenza Hla B*0702mentioning
confidence: 99%
“…Next, the cells were incubated with a 10-fold serial dilution of the peptides in R10F for 1 h at 37°C, washed once in R10F, and used as target cells in a 51 Cr release assay. The HLA-A2-, -A3-, -B27-, and -B35-restricted influenza A virus-specific CTL clones were previously described (23)(24)(25), while the HLA-A1-and -B8-restricted influenza A virus-specific CTL clones were established, as described previously (25).…”
Section: Preparation Of Target Cells For 51 Cr Release Assaymentioning
confidence: 99%
“…The EBNA3C epitope becomes readily available for CTL recognition when inserted into the context of the nucleoprotein, thus suggesting the presence in the C terminus of sequences relevant for localization and/or processing by resident proteases. It has been already reported that the epitope 383-391 from the nucleoprotein of influenza A virus can be processed and presented in TAP-deficient cells (38). Moreover, other epitopes carried by this protein appear to follow different routes for processing (13).…”
Section: Discussionmentioning
confidence: 95%